2020
DOI: 10.3390/rs12172700
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Suaeda salsa Spectral Response to Salt Conditions in Coastal Wetlands: A Case Study in Dafeng Elk National Nature Reserve, China

Abstract: This paper reports on monitored Suaeda salsa spectral response to salt conditions in coastal wetlands, using spectral measurements and remotely sensed algorithms. Suaeda salsa seedlings were collected from the Dafeng Elk National Nature Reserve (DENNR) in Jiangsu Province, China. We treated 21 Suaeda salsa seedlings planted in pots with 7 different salt concentrations (n = 3 for each concentration) to assess their response to varying salt conditions. Various plant growth indicators, including chlorophyll conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…However, when we measured the reflectance of the canopy spectrum, we found that the reflectance of the canopy spectrum may also be related to light conditions, soil types, and crop varieties [41]. More studies are needed to verify our findings [42]. (2) We constructed thirteen new vegetation indices.…”
Section: Discussionmentioning
confidence: 81%
“…However, when we measured the reflectance of the canopy spectrum, we found that the reflectance of the canopy spectrum may also be related to light conditions, soil types, and crop varieties [41]. More studies are needed to verify our findings [42]. (2) We constructed thirteen new vegetation indices.…”
Section: Discussionmentioning
confidence: 81%
“…The Yancheng Dafeng Elk Nature Reserve (Longitude: 120°47′~120°53′ E, Latitude: 32°59′~33°03′ N) is located in the eastern part of Jiangsu province, near to the Yellow Sea, and occurs at the transition zone between a subtropical and a warm temperate zone ( Figure 1 ). Covering an area of 2666 ha, it is the largest elk nature reserve worldwide with the largest number of wild elk populations [ 34 ]. In January 2002, the reserve was included in the list of important international wetlands by the United Nations Wetland Conservation Organization as a permanent protected area.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, multivariate data analysis can help uncover useful information hidden within it ( Maione et al, 2019 ), especially for massive datasets from sensors. Machine learning methods showed the excellent data mining ability in hyperspectral data mining ( Yang et al, 2020 ; Najafabadi, 2021 ; Weng et al, 2021 ), and the combination between them can be exploited as a competent tool in plant science ( Greener et al, 2022 ) such as early stress detection ( Gu et al, 2019 ; Lu et al, 2020 ; Zheng et al, 2020 ), unsound kernel identification ( Liang et al, 2020 ; Zhang et al, 2021a ), and the evaluation of nutrition content ( Zhang et al, 2020a , b ; Najafabadi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%